2016
DOI: 10.1111/cch.12365
|View full text |Cite
|
Sign up to set email alerts
|

Visual–motor integration performance in children with severe specific language impairment

Abstract: A small subgroup of children with severe SLI will also have poor VMI skills. The best predictor of poor VMI is receptive language scores on the Clinical Evaluation of Language Fundamentals. Children with poor receptive language performance may benefit from VMI assessment and multidisciplinary management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Conversely, one study found no significant differences between genders for children four to 14 years old with severe language impairment [ 55 ]. There was no significant difference in mean performance between males and females; however, children with poor VMI skills also had poor receptive language skills [ 55 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, one study found no significant differences between genders for children four to 14 years old with severe language impairment [ 55 ]. There was no significant difference in mean performance between males and females; however, children with poor VMI skills also had poor receptive language skills [ 55 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Conversely, one study found no significant differences between genders for children four to 14 years old with severe language impairment [ 55 ]. There was no significant difference in mean performance between males and females; however, children with poor VMI skills also had poor receptive language skills [ 55 ]. VMI deficits in children with a language impairment component are common due to the interconnection between motor, visual, and integration difficulties.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…At present, there is rare research on the visual‐motor coordination with digitalised equipment [9–12]. For example, David et al .…”
Section: Introductionmentioning
confidence: 99%